The Role of P2X7 Receptor in Alzheimer’s Disease - Francistiová, Linda; Bianchi, Carolina; Di Lauro, Caterina; Sebastián-Serrano, Álvaro; de Diego-García, Laura; Kobolák, Julianna; Dinnyés, András; Díaz-Hernández, Miguel (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease characterized by a progressive cognitive decline associated with global brain damage. Initially, intracellular paired helical filaments composed by hyperphosphorylated tau and extracellular deposits of amyloid-β (Aβ) were postulated as the causing factors of the synaptic dysfunction, neuroinflammation, oxidative stress, and neuronal death, detected in AD patients. Therefore, the vast majority of clinical trials were focused on targeting Aβ and tau directly, but no effective treatment has been reported so far. Consequently, only palliative treatments are currently available for AD patients. Over recent years, several studies have suggested the involvement of the purinergic receptor P2X7 (P2X7R), a plasma membrane ionotropic ATP-gated receptor, in the AD brain pathology. In this line, altered expression levels and function of P2X7R were found both in AD patients and AD mouse models. Consequently, genetic depletion or pharmacological inhibition of P2X7R ameliorated the hallmarks and symptoms of different AD mouse models. In this review, we provide an overview of the current knowledge about the role of the P2X7R in AD.